Emerging technology and techniques - Gopi Naveen Chander; B Mutukumar; C Sasikala; N Dhanasekar (Wolters Kluwer Medknow Publications, 2015)
A technique of fabricating feldspathic porcelain pressable ingots was proposed. A 5 ml disposable syringe was used to condense the powder slurry. The condensed porcelain was sintered at 900΀C to produce porcelain ingots. The fabricated porcelain ingots were used in pressable ceramic machines. The technological advantages of pressable system improve the properties, and the fabricated ingot enhances the application of feldspathic porcelain.